Reputation: 111
Is there a way to "propagate" a conjugate into a sum?
from sympy import *
k = symbols('k', cls=Idx)
K = symbols('K', type=Integer)
g = IndexedBase('g')
omega = symbols('\omega', real=True)
s = summation(exp(I*omega*k)*g[k], (k,0,K))
sconj=s.conjugate()
Now sconj
is
How can I turn this expression into the one below? That is, apply the conjugate on the terms rather than the sum.
(Which I off course can obtain by taking the conjugate of the terms when creating the summation
summation((exp(I*omega*k)*g[k]).conjugate(), (k,0,K))
but think of the general case where this may be not so straightforward.)
Upvotes: 0
Views: 40
Reputation: 111
Just in case someone else runs into this.
It is required to set the summation bound as Real, so changing the definition of K
to
K = symbols('K', type=Integer, real=True)
did the trick.
Upvotes: 1